THE EFFECTS OF INDIVIDUAL ATTITUDES, ACADEMIC SUPPORT, AND SOCIAL SUPPORT TOWARDS ENTREPRENEURIAL INTENTIONS IN MANAGEMENT STUDY PROGRAM OF ECONOMICS & BUSINESS FACULTY AT X UNIVERSITY - R. Achamd Drajat Aji; Sugiyo; Heri Suharta (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This study aims to analyze the effect of individual attitudes, academic support, and social support on entrepreneurial intentions. The type of research method used is an explanatory survey. The population in this study were 378 students. Sample selection using simple random sampling technique and obtained a sample of 192. The statistical data analysis used is validity, reliability, classic assumption test, coefficient of determination, multiple regression analysis, and hypothesis testing with ANOVA. Based on the results of data processing shows that individual attitudes (X1), academic support (X2), and social support (X3) have a significant effect both simultaneously and partially on entrepreneurial intentions (Y). Thus the model used in this study is fit. Individual attitudes, academic support, and social support have a strong enough relationship with entrepreneurial intentions (Y) significantly, with a positive correlation. The coefficient of determination is 0.318 which means that individual attitudes (X1), academic support (X2), and social support (X3) contribute 31.8% to entrepreneurial intentions (Y), while the remaining 68.2% is influenced by other variables not examined in this research. The results of the partial study also found that the dominant variable affecting entrepreneurial intentions was the social support variable with a positive correlation